2004
DOI: 10.2105/ajph.94.12.2132
|View full text |Cite
|
Sign up to set email alerts
|

Very Low Birthweight in African American Infants: The Role of Maternal Exposure to Interpersonal Racial Discrimination

Abstract: The lifelong accumulated experiences of racial discrimination by African American women constitute an independent risk factor for preterm delivery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
295
4

Year Published

2005
2005
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 357 publications
(310 citation statements)
references
References 31 publications
6
295
4
Order By: Relevance
“…Research on stressors for African American women reveals that during pregnancy, they anticipate their children experiencing racial inequalities which includes the possibility of negative police interactions. The psychosocial stress produced by racial and gendered inequities is associated with disproportionately higher rates of adverse birth outcomes among African American women, regardless of their socioeconomic position [11][12][13][14][15][16]. Studies have also revealed significant associations between intersectional racial and gendered stress (that includes parenting demands) and antenatal depression [17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Research on stressors for African American women reveals that during pregnancy, they anticipate their children experiencing racial inequalities which includes the possibility of negative police interactions. The psychosocial stress produced by racial and gendered inequities is associated with disproportionately higher rates of adverse birth outcomes among African American women, regardless of their socioeconomic position [11][12][13][14][15][16]. Studies have also revealed significant associations between intersectional racial and gendered stress (that includes parenting demands) and antenatal depression [17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, research has shown that clinically relevant stress-related biomarkers are higher in black than in white people, and these racial differences are not explained by SES. [42][43][44][45] For children and adolescents, discrimination related to race, ethnicity, or SES may affect the child directly. Timing of exposure to discrimination may alter its influence, with adolescents having the greatest likelihood of understanding the nature and meaning of discriminatory remarks and actions of others.…”
Section: Racial and Other Forms Of Discriminationmentioning
confidence: 99%
“…Researchers have found that lifelong accumulated experiences of racial discrimination are an independent risk factor for preterm delivery. 45 For researchers attempting to assess discrimination, self-report has been the traditional approach. Recent reviews have documented the strengths and limitations of several measures of perceptions of race-or ethnicity-based discrimination.…”
Section: Racial and Other Forms Of Discriminationmentioning
confidence: 99%
“…It has been firmly established that infant birth weight is not only a primary determinant of infant mortality, but that the one percent of very low birth weight occurrences (<1,500 g) accounts for more than half of all neonatal deaths and 63% of the Black-White gap of US infant mortality [1,2]. Healthy People 2010 [3] objectives include reducing the infant mortality rate to no more than 4.5/1,000 live deliveries, a reduction in incidence of moderately low birth weight (<2,500 g) to 5.0% and a reduction in incidence of very low birth weight babies (<1,500 g) to 0.9% [4].…”
Section: Introduction and Purposementioning
confidence: 99%